Efficient Synthesis of N‐Acylureas Using Copper Oxide Supported on Magnetic Nanoparticles in Deep Eutectic Solvent. Issue 1 (3rd January 2018) - Abbasi, Sepideh; Miraki, Maryam Kazemi; Radfar, Iman; Karimi, Meghdad; Heydari, Akbar
Abstract: A unique combination of deep eutectic solvent (the combination of urea with choline chloride) and magnetic CuO@γ‐Fe2 O3 nanoparticles as a green magnetic nanocatalyst promotes the synthesis of N‐acylureas from reaction carbodiimides with carboxylic acids. This reaction gives the corresponding N‐acylurea derivatives in good to high yields. Easy preparation and separation, inexpensive, insensitivity to moisture and reusability of the catalyst are significant features of this method. Abstract : A unique combination of deep eutectic solvent (the combination of urea with choline chloride) and magnetic CuO@γ‐Fe2 O3 nanoparticles as a green magnetic nanocatalyst promotes the synthesis of N‐acylureas from reaction carbodiimides with carboxylic acids.